Pembelajaran Bermakna Untuk Mencapai Pendidikan Karakter - Ady Ferdian Noor (Anterior Jurnal, 2013)
National Education Minister's Regulation Number 41 of 2007: Process Standards for Primary and Secondary Education Units: Organizing activities to achieve Basic Competencies (KD) which are carried out interactively, inspiratively, fun, challenging, motivating students to enjoy actively, and provide sufficient space for initiative, creativity, and independence in accordance with the talents, interests and physical and psychological development of students. Learning activities in education are not just a process of delivering material, but will be done to make character, civilization, and promote the quality of life of students. Learning is directed to encourage education and the specific responsibilities of each individual who is able to become lifelong learners and realize a learning community. The principle of learning to underlie every step of learning to achieve character education, Based on behavioristic flow, learning is essential to building relationships with the Stimulus-Respons (S-R) response. Learning is an effort to display as many S-R relationships as possible. The learning steps are meaningful as follows: 1) Learning through the surrounding environment; 2) Make a concept map; 3) Give answers for prison groups in small groups (4-5 people); 4) Lessons for making joint Decisions based on each experience; 5) Inquiry; 6) Carry out exercises.